Asymptomatic bacteriuria, to treat or not to treat (Ósmosis Revista Médica Estudiantil, 2022)
Asymptomatic bacteriuria (ASB) is a common incidental finding in hospitals and health facilities during general examination of patients. Due to the new trend of giving antibiotic treatment without regulation in certain infections, it is important stablishing criteria to avoid over usage of antibiotics during the general or intrahospitalary examination of patients. This text summarizes the main characteristics of ASB, diagnostic criteria, definitions and assessment of treatment in defined populations.